Using Generative Adversarial Networks as a Fast Forward Operator for Hydrogeological Inverse Problems - Dagasin, Yasin; Juda, Przemyslaw; Renard, Philippe (My University, 2020)
Subsurface characterization using inverse techniques constitutes one of the fundamental elements of hydrogeological modeling applications. Available methods to solve inverse problems rely on a forward operator that predicts state variables for a given set of subsurface parameters. As the number of model parameters to be estimated increases, forward operations incur a significant computational demand. In this paper, we investigate the use of conditional generative adversarial networks (cGAN) as an emulator for the forward operator in the context of a hydrogeological inverse problem. We particularly investigate if the cGAN can be used to replace the forward operator used in the adaptive importance sampling method posterior population expansion (PoPEx) with reasonable accuracy and feasible computation requirement. The cGAN model trained on channelized geological structures has shown that the cGAN is able to reproduce the state variables corresponding to a certain parameter field. Hence, its integration in PoPEx yielded satisfactory results. In terms of the computational demand, the use of cGAN as a surrogate forward model reduces the required computational time up to 80% for the problem defined in the study. However, the training time required to create a model seems to be the major drawback of the method.